An investigation into the readability of the grade 10 physical science textbooks : a case study - Van Heerden, Lesley Lynne (Rhodes University, Faculty of Education, Department of Education, 2010)
In her newsletter "Curriculum News, Improving the Quality of Learning and Teaching: Planning for 2010 and Beyond" , Mrs Angie Motshekga, MP, Minister of Basic Education, positions the textbook very definitely as central to the curriculum and states that it is one of the most effective tools through which to deliver the curriculum and support assessment. Acknowledging the importance of the accessibility of textbooks for the South African classroom audience, this study has sought to investigate the readability of the chemistry section of grade 10 science textbooks. Readability research is concerned with the relationship between the textbook, the reader and the context in which the book is read; research supports the use of both classical quantitative measures and a qualitative cognitive-structural form of analysis to investigate this relationship. The research design is a mixed method one where quantitative and qualitative data were collected simultaneously: the methodical application of selected readability formulae gave rise to quantitative data while the line-by-line textual analysis, tracing cognitive-structural aspects, and focus-group discussions with teachers gave rise to the qualitative data. The results of the merged data analysis were then interpreted together to provide a better understanding of the readability of the texts for a South African audience. The results of the investigation reveal that readability is greatly impaired for a number of reasons, the primary one being a lack of articulation between the textbook writers/editors and the audience for which they are writing and preparing the texts. This is particularly reflected in the inadequate preparation of the material for the English Second Language reader, as certain textbooks are completely out of their reach. Furthermore, this lack of articulation can be traced to the lack of time available for piloting the textbooks: an invaluable intervention in the process of textbook production.
Keywords: Textbooks -- South Africa -- Readability; Readability (Literary style); Science -- Study and teaching (Secondary) -- Case studies